2020
DOI: 10.1111/bjhp.12416
|View full text |Cite
|
Sign up to set email alerts
|

Baring all: The impact of the hospital gown on patient well‐being

Abstract: Objectives. The importance of personalized and dignified care is increasingly being recognized in health care policy and practice. Despite the known impact of clothing on social identity and self-expression, the impact of hospital clothing on patient well-being has been widely overlooked. Patients are often required to wear hospital clothing, commonly a backless gown, during medical procedures and surgeries. The impact of wearing patient clothing on well-being, during this time of vulnerability, was explored.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…All participants reported high rates of satisfaction and decrease in embarrassment (12). Another study analyzed the impact of wearing patient gowns on well-being and concluded that the current design of the hospital gown is not fit for purpose and impacts negatively on patient well-being (6). Both papers, especially the latter, reaffirm the need for hospital gown change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All participants reported high rates of satisfaction and decrease in embarrassment (12). Another study analyzed the impact of wearing patient gowns on well-being and concluded that the current design of the hospital gown is not fit for purpose and impacts negatively on patient well-being (6). Both papers, especially the latter, reaffirm the need for hospital gown change.…”
Section: Discussionmentioning
confidence: 99%
“…The palpable dichotomy between the pristine white coat of a physician and the revealing patient gown is another barrier and perpetuates the hierarchy within care institutions (3 5). Clothing buffers us against environmental change and protects us in social contexts (6). To paraphrase the designer, Coco Chanel, “Clothing has 2 purposes: comfort and love.” A growing body of literature highlights external factors that impact patients’ sense of comfort in the hospital (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Our findings about patients' priorities reinforce results from a 2020 multimethod study consisting of semistructured interviews and an online survey that focused specifically on patients' perspectives on gown wearing. 3 Regarding function, most patients reported that they struggled to put the gown on by themselves (64%) and that it did not fit (70%). With respect to dignity and comfort, most patients reported feeling exposed (72%), self-conscious (60%) and uncomfortable (57%).…”
Section: Discussionmentioning
confidence: 99%
“…Hospital gowns can convey a sense of exposure, discomfort, disempowerment, embarrassment, reduced self-esteem and compromised dignity. [1][2][3] As a result, governments, researchers, celebrity designers and private health care systems have made efforts to redesign the standard gown to improve patients' experiences. [4][5][6][7] However, design innovations have not been met with substantial market uptake; new designs are still being developed and tested.…”
mentioning
confidence: 99%